2019
DOI: 10.1038/s41598-019-48077-5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Intrauterine Pressure On Embryo Retention In A Catheter After Embryo Transfer

Abstract: The retention of the embryo in the transfer catheter after embryo transfer (ET) during in vitro fertilization is a very common phenomenon, encountered by even the most experienced operators, and embryos retained in the transfer catheter or its sleeve require a repeat transfer. The exact mechanism of embryo retention has not been explained. Therefore, the present study aimed to investigate the mechanism of embryo retention in the catheter during embryo transfer by using a transparent uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The exact mechanism of embryo retention has not been explained. Therefore, Kozikowska et al's study aimed to investigate the mechanism of embryo retention in the catheter during embryo transfer by using a transparent uterus model equipped with pressure sensors and a video recorder 22 . Their results indicated that pressure changes in the uterine cavity during ET can influence the distribution of the transferred fluid containing the embryo.…”
Section: Retention Of Embryos At Etmentioning
confidence: 99%
“…The exact mechanism of embryo retention has not been explained. Therefore, Kozikowska et al's study aimed to investigate the mechanism of embryo retention in the catheter during embryo transfer by using a transparent uterus model equipped with pressure sensors and a video recorder 22 . Their results indicated that pressure changes in the uterine cavity during ET can influence the distribution of the transferred fluid containing the embryo.…”
Section: Retention Of Embryos At Etmentioning
confidence: 99%